The Status of the National HIV Surveillance System, United States, 2013. (July 2014) - Cohen, Stacy M.; Gray, Kristen Mahle; Ocfemia, M. Cheryl Bañez; Johnson, Anna Satcher; Hall, H. Irene
The burden of HIV disease in the United States is monitored by using a comprehensive surveillance system. Data from this system are used at the federal, state, and local levels to plan, implement, and evaluate public health policies and programs. Implementation of HIV reporting has differed by area, and for the first time in early 2013, estimated data on diagnosed HIV infection were available from all 50 states, the District of Columbia, and six U.S. dependent areas. The newly available data for the entire U.S. as well as several other key changes to the surveillance system support the need to provide an updated summary of the status of the National HIV Surveillance System.